2015
DOI: 10.1039/c4ta06715k
|View full text |Cite
|
Sign up to set email alerts
|

A high-rate aqueous symmetric pseudocapacitor based on highly graphitized onion-like carbon/birnessite-type manganese oxide nanohybrids

Abstract: We present a study on the pseudocapacitive properties of birnessite-type MnO 2 grafted on highly graphitized onion-like carbon (OLC/MnO 2 ). In a three-electrode setup, we evaluated two different substrates, namely a platinum disc and nickel foam. The OLC/MnO 2 nanohybrid gave large specific capacitance (C sp ) of 295 and 323 F g -1 (at 1 A g -1 ) for the Pt disc and Ni foam, respectively. In addition, the Ni foam substrate exhibited much higher rate capability (power density) than the Pt disc. A symmetrical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 76 publications
2
59
0
1
Order By: Relevance
“…Wang et al [123] reported the (MnO 2 )/onion-like carbon (OLC)-based nanocomposite electrode with the specific capacitance of 177.5 F g −1 . Also, Makgopa et al [124] synthesized nano-diamond-derived carbon onion with MnO 2 composite electrodes ( Fig. 5a, b) and it showed the specific capacitance of 335-408 F g −1 at current densities of 0.1-0.3 A g −1 .…”
Section: Carbon Onionmentioning
confidence: 99%
“…Wang et al [123] reported the (MnO 2 )/onion-like carbon (OLC)-based nanocomposite electrode with the specific capacitance of 177.5 F g −1 . Also, Makgopa et al [124] synthesized nano-diamond-derived carbon onion with MnO 2 composite electrodes ( Fig. 5a, b) and it showed the specific capacitance of 335-408 F g −1 at current densities of 0.1-0.3 A g −1 .…”
Section: Carbon Onionmentioning
confidence: 99%
“…The CNO hybrid systems were used as materials for hybrid charge‐storage devices ,. This type of modification was also applied to the preparation of CNO/RuO 2 ,, CNO/MnO 2 ,, and CNO/CuO composites ,,. A novel composite of CNO/Co 3 O 4 was synthesized using ionic liquid as a carbon and nitrogen source through a facile carbothermic reduction followed by a low‐temperature oxidation method .…”
Section: Covalent and Non‐covalent Functionalization Of Cnosmentioning
confidence: 99%
“…Comparing the suitability of activated carbona nd carbon onions as substrates for hydrothermally grown manganese oxide showeds imilar findings like the studies using ALD. Carbon onions provided good conditions for homogenous deposition of birnessite-type manganese oxide, [40] whereas blockingo fi nternal surface area was observed for activated carbon.H owever,c onsidering that the hydrothermala pproachi sl essp recise compared to ALD,t he minimum accessible pore size was bigger,a nd as ealing of the www.chemeurj.org 2018 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim activatedc arbon particles was already observed at lower mass loadings. [16b] The study furtherc oncluded that the degree of carbon onion graphitization had as ubstantial impact on the electrochemical properties of the hybrid materials.…”
Section: Strategy 1: Thin Metal Oxide Coating On a Carbon Substratementioning
confidence: 99%